Brand® new theology: the Wal-Martization of T.D. Jakes and the new Black church - MacGee, Paula L. (Orbis Books, 2017)
T.D. Jakes, woman thou art loosed, and the new Black church -- The Black church vs. the new Black church -- Prosperity theology, the new Black church, and T.D. Jakes -- T.D. Jakes as pastor, CEO, and theologian of prosperity 95 -- Bishop Jakes and the brand for women-woman thou art loosed -- "Keeping it real!